Are You My Host? An Overview of Methods Used to Link Bacteriophages with Hosts - Paul Hyman (Viruses)
Until recently, the only methods for finding out if a particular strain or species of bacteria could be a host for a particular bacteriophage was to see if the bacteriophage could infect that bacterium and kill it, releasing progeny phages. Establishing the host range of a bacteriophage thus meant infecting many different bacteria and seeing if the phage could kill each one. Detection of bacterial killing can be achieved on solid media (plaques, spots) or broth (culture clearing). More recently, additional methods to link phages and hosts have been developed. These include methods to show phage genome entry into host cells (e.g., PhageFISH); proximity of phage and host genomes (e.g., proximity ligation, polonies, viral tagging); and analysis of genomes and metagenomes (e.g., CRISPR spacer analysis, metagenomic co-occurrence). These methods have advantages and disadvantages. They also are not measuring the same interactions. Host range can be divided into multiple host ranges, each defined by how far the phage can progress in the infection cycle. For example, the ability to effect genome entry (penetrative host range) is different than the ability to produce progeny (productive host range). These different host ranges reflect bacterial defense mechanisms that block phage growth and development at various stages in the infection cycle. Here, I present a comparison of the various methods used to identify bacteriophage-host relationships with a focus on what type of host range is being measured or predicted.